THE IMPACT OF PODCASTS ON EFL STUDENTS’ LISTENING COMPREHENSION - Abdulrahman, Tryanti; Basalama, Nonny; Widodo, Mohammad Rizky (Universitas Negeri Makassar, 2018)
This research has objective to investigate students’ listening comprehension through the use of podcast in EFL classroom. 60 high school students in Indonesia were taken as sample for this research with distribution of 30 students in experiment class and 30 students in control class. The samples were taken by using cluster random sampling. Quasi-experimental method with the post-test only control group design was applied in this research. In addition, a survey questionnaire was administered to experimental group to explore their perception on the use of podcast instruction in teaching listening. Findings revealed that there is a significant difference of post-test score between two groups, favoring experimental group. Data analysis using one way ANOVA showed significance value (sig. 0.010) is lower than < 0.05 which interpreted that Podcast has significant impact on students’ listening comprehension. Additionally, the result of questionnaire indicated that students have positive attitude toward the use of podcast in listening classroom. Students perceived that podcasts provided authentic materials, interesting activities including listening exercises and meaningful tasks for them so they felt more motivated to learn English. This study recommended that teacher may utilize podcast in teaching listening considering its effectiveness as technology based learning tool.